On reducing the risk of inadvertent release of ski bindings - Brown, C. A.; Braun, N. E.; Lagassey, J.; Madura, J. M. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The objective of this paper is to present a multifaceted approach to reducing the risk of inadvertent release (IR) in alpine skiing, especially, although not exclusively, for competitors. Avoiding IR is important for reducing the risk of two types of injury: those that result from IR, and those that result from elevated binding settings that are used to avoid IR. Severe trauma, including paralysis and death, are known to result from IR. Currently, elevated settings are the only apparent means available to reduce the risk of inadvertent release. The unintended consequence of elevated settings is increased risk of leg and knee injuries. Despite this increased risk, in many races and training situations, IR occurs more often than leg and knee injuries. Previous work shows loading direction to be a problem for heel retention. Generally, causes of IR and remedies are both poorly understood.